Irese Laundry / Wardatul Raihan Ahmad ... [et al.] - Ahmad, Wardatul Raihan; Baharin, Kamariah; Haron, Hasraummi; W. Mahmood, Wan Nurul Hafiza; Abdur Rafar, Shahida Hannani (Faculty of Accountancy, 2002)
Irise Laundry is a business of laundry and the business will be started on Is January 2003. Services that will be provided are normal washing, express dry cleaning, ironing, comforters and curtains. This business location is situated at No.8, Jalan Pinang E18/ E Section 18,40 000 Shah Alam, Selangor Darul Ehsan. This location is situated in resident areas. Therefore, it will have a great potential market for this business. Besides that, this area is near Akasia and Cemara College. Moreover, it has less competitors as compared to other business and services. This year economic situation is more stable, therefore we expect that in 2003 Malaysia's economic will continue to growth. As the country prospers, more people are employed, making standard living of people in Malaysia getting better each year. Furthermore our ways of thinking has changed people no longer assume that laundry is only necessary for wealthy society. We believe that our business have potential in this millennium especially in urban area because people are busy with studies and works. As the consequences they have limited time to do house chores like washing clothes. Therefore they prefer to send their clothes to the nearest laundry shop. Related to this situation, we focus to students and residents of Section 18, Shah Alam. Another factors that influencing us to choose this laundry services is because lack of competitors in Section 18, Shah Alam making it easier for us as a new entrepreneur to engage in the business because this service do not require large capital and professional workers.